Evaluating the Nexus among Early Breastfeeding Initiation, Exclusive Breastfeeding Practices, and Neonatal Weight Gain - Putri, Pratiwi Syah; Febri Yusnanda; WildaYunita; Nuriatus Sakdiah, (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Early Initiation of Breastfeeding (EIB) involves placing a newborn in skin-to-skin contact with the mother immediately after birth to initiate breastfeeding within the first hour of life. This clinical procedure serves as a foundational pillar for neonatal survival, successful exclusive breastfeeding, and metabolic adaptation. Globally and nationally, ensuring steady early anthropometric growth remains a priority to eliminate neonatal vulnerability. Objectives: This study aimed to analyze the operational relationship between the implementation of Early Initiation of Breastfeeding and newborn weight gain trajectory in a clinical care setting. Methods: This research employed an analytical descriptive approach using a cross-sectional study design conducted at Sundari Hospital, Medan. The sample size consisted of 35 mother-infant pairs recruited using a total sampling technique. Data collection targeted EIB adherence profiles and post-birth weekly anthropometric shifts, which were evaluated through Chi-Square statistical validation and multivariate logistic adaptation models. Results: The univariate analysis showed that EIB was successfully established in 80.0% of deliveries, and 71.4% of neonates reached the optimal weight gain index ( ≥500 grams/week). The cross-tabulation matrix revealed that 85.7% of infants who underwent immediate EIB achieved optimal weight gain trajectories, compared to only 14.3% in the non-EIB cohort. The statistical evaluation confirmed a significant clinical relationship between EIB execution and optimal neonatal weight gain (p = 0.001, OR = 4.85). Conclusions: Immediate implementation of EIB after delivery significantly speeds up newborn weight recovery and minimizes postpartum weight loss. Healthcare institutions must enforce strict baby-friendly hospital initiatives to ensure EIB protocols are maintained across all delivery settings.